Influence of sports specificity on motor coordination in brazilian children - Lucas Savassi Figueiredo; Rodrigo Fábio Bezerra da Silva; Lucas de Castro Ribeiro; Thaís da Silva Sérvio; João Vitor Alves Pereira Fialho; Juliane Venturelli Silva Lima; Henrique de Oliveira Castro; Fabiano de Souza Fonseca (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective: this study analyzed the influence of the specificity of sports practice on Brazilian children's motor coordination levels.